2021
DOI: 10.3389/fnins.2021.682247
|View full text |Cite
|
Sign up to set email alerts
|

Decreased MEF2A Expression Regulated by Its Enhancer Methylation Inhibits Autophagy and May Play an Important Role in the Progression of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by amyloid plaques and neurofibrillary tangles which significantly affects people’s life quality. Recently, AD has been found to be closely related to autophagy. The aim of this study was to identify autophagy-related genes associated with the pathogenesis of AD from multiple types of microarray and sequencing datasets using bioinformatics methods and to investigate their role in the pathogenesis of AD in order to identify novel strategies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…had overactivation of JUN, which is implicated in cytokine production and microglia polarization [36]. Macrophage activation suppressor ETV5 and microglia negative regulator MEF2A in Alzheimer's disease [37,38] were enriched in the Mg‐TAM_hom. cluster (Figure 4A), sustaining the inactive state of Mg‐TAM_hom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…had overactivation of JUN, which is implicated in cytokine production and microglia polarization [36]. Macrophage activation suppressor ETV5 and microglia negative regulator MEF2A in Alzheimer's disease [37,38] were enriched in the Mg‐TAM_hom. cluster (Figure 4A), sustaining the inactive state of Mg‐TAM_hom.…”
Section: Resultsmentioning
confidence: 99%
“…Delineating TAM diversity in glioma using scRNA-seq 125 Delineating TAM diversity in glioma using scRNA-seq 127 Delineating TAM diversity in glioma using scRNA-seq 129 disease [37,38] were enriched in the Mg-TAM_hom. cluster (Figure 4A), sustaining the inactive state of Mg-TAM_hom.…”
Section: Specific Regulons Across Myeloid Clusters Dictate a Distinct...mentioning
confidence: 99%
“…Many target genes of miR-6240 have been proposed to be related to AD etiopathogenesis, including serine and arginine-rich splicing factor 1 ( SRSF1 ), hypoxia-inducible factor-1α ( HIF1α ), mesenchyme homeobox 2 ( MEOX2 ), cAMP-responsive element-binding protein 1 ( CREB1 ), pericentriolar material-1 ( PCM1 ), coiled-coil containing protein kinases ( ROCK2 ), synaptosomal-associated protein 23 ( SNAP23 ), and myocyte enhancer factor 2A ( MEF2A ). These genes are involved in plaque deposition, tau protein biosynthesis, neuronal dysfunction, neuroinflammation, autophagy, and other pathological processes related to AD ( Chakravarthy et al, 2013 ; Soto et al, 2016 ; Muhammad et al, 2019 ; Adeyemi et al, 2021 ; Li et al, 2021 ; Weber and Herskowitz, 2021 ). SRSF1 is a member of the serine/arginine-rich proteins family, which is involved in the process of exon selection and mRNA output and localization.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer’s disease is also characterized by downregulation of autophagy-related-genes that are regulated by MEF2A. Methylated-microarray analysis performed by Li and colleagues [ 105 ] showed that methylation level of the enhancer region of MEF2A was increased in AD. It can be speculated that the increased methylation reduces the expression of MEF2A and, as a consequence, downregulates autophagy-related genes that are closely linked to AD pathology.…”
Section: Mef2 In Neuronal Degenerationmentioning
confidence: 99%